Decision Tree With Only Two Musculoskeletal Sites to Diagnose Polymyalgia Rheumatica Using [18F]FDG PET-CT - Flaus, Anthime; Amat, Julie; Prevot, Nathalie; Olagne, Louis; Descamps, Lucie; Bouvet, Clément; Barres, Bertrand; Valla, Clémence; Mathieu, Sylvain; Andre, Marc; Soubrier, Martin; Merlin, Charles; et al. (Frontiers in Medicine, 2021)
Abstract The aim of this study was to find the best ordered combination of two FDG positive musculoskeletal sites with a machine learning algorithm to diagnose polymyalgia rheumatica (PMR) versus other rheumatisms in a cohort of patients with inflammatory rheumatisms. Methods This retrospective study included 140 patients who underwent [18F]FDG PET-CT and whose final diagnosis was inflammatory rheumatism. The cohort was randomised, stratified on the final diagnosis into a training and a validation cohort. FDG uptake of 17 musculoskeletal sites was evaluated visually and set positive if uptake was at least equal to that of the liver. A decision tree classifier was trained and validated to find the best combination of two positives sites to diagnose PMR. Diagnosis performances were measured first, for each musculoskeletal site, secondly for combination of two positive sites and thirdly using the decision tree created with machine learning. Results 55 patients with PMR and 85 patients with other inflammatory rheumatisms were included. Musculoskeletal sites, used either individually or in combination of two, were highly imbalanced to diagnose PMR with a high specificity and a low sensitivity. The machine learning algorithm identified an optimal ordered combination of two sites to diagnose PMR. This required a positive interspinous bursa or, if negative, a positive trochanteric bursa. Following the decision tree, sensitivity and specificity to diagnose PMR were respectively 73.2% and 87.5% in the training cohort and 78.6% and 80.1% in the validation cohort. Conclusion Ordered combination of two visually positive sites leads to PMR diagnosis with an accurate sensitivity and specificity versus other rheumatisms in a large cohort of patients with inflammatory rheumatisms.